Can AI Be Used as Evidence in Medical Malpractice Lawsuits? The Legal and Ethical Frontier - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into clinical practice, from diagnostic algorithms to surgical robotics, is rapidly transforming healthcare. Wh...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care